Analysis of Play Therapy in Play Activities in Early Childhood - Isabella Hasiana; Mudhar Mudhar; Elia Firda Mufidah (Child Education Journal, 2023)
This research aims to analyze the implementation of play therapy embedded in play activities in Kindergarten B children at Lintang Kindergarten Surabaya. Play therapy is a therapeutic activity given to children to overcome problems related to cooperation, socialization and emotions. This play therapy approach places more emphasis on non-verbals. This means that children aged 2 to 12 years can freely express the feelings they experience, through playing with toys, sand, dolls, clay, art, dance and natural music. This research uses descriptive qualitative research methods. The research population was PAUD PG teachers at Lintang Kindergarten Surabaya. The research sample consisted of 2 teachers who taught class B. The choice of class B teachers was because, from the results of observations made, problems related to student socialization most often emerged in class B. The results of the research concluded that with play therapy, children become it is easier to express his feelings, becomes more relaxed and happy.